Spatial Study of Eel Larva Habitat in Ciletuh Bay Waters, Sukabumi Regency, West Java - Annisa, Illa; Supriatna, Supriatna; Shidiq, Iqbal Putut Ash; Indra, Tito Latif; Gracia, Enrico (Jambura Geoscience Review, 2024)
Eels (Anguilla spp.) are highly nutritious fish that are widely consumed. Ciletuh Bay, situated opposite the Indian Ocean, is a natural habitat for eel larvae. The migration of eel larvae is influenced by various oceanographic factors, including salinity, sea surface temperature, and chlorophyll-a. In order to support fisheries activities in Sukabumi Regency, it is important to identify the optimal habitat for eel larvae and obtain information about their abundance. This study used remote sensing techniques and two algorithms, the Cilamaya Algorithm to estimate salinity and the Wibowo Algorithm to estimate chlorophyll-a. The study was conducted during the wet, dry, and transitional months of 2019 and 2020 in Ciletuh Bay. The potential areas for eel larvae were found to be concentrated at the mouth of the river during the wet month, at the estuary and the shore during the dry month and the first transitional month, and tended to spread during the second transitional month. The largest potential area was found during the dry month of 2019, covering an area of 3.44 km2, but the potential was more stable during the wet months.